2008
DOI: 10.1510/icvts.2008.179192
|View full text |Cite
|
Sign up to set email alerts
|

Significance of morphological and electrophysiological left ventricular restoration in idiopathic dilated cardiomyopathy

Abstract: Treatment of non-ischemic dilated cardiomyopathy (NIDCM) remains a challenge. Morphological left ventricular (LV) restoration such as septal anterior ventricular exclusion (SAVE) can be effective in treating NIDCM; however, residual electrophysiological disorders such as atrioventricular and intraventricular conduction disturbances become apparent in the form of atrial fibrillation (AF) and LV dyssynchrony, which deteriorate postoperative LV function. Thus, the combination of morphological and electrophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…CRT-P/CRT-D implantation might be useful as a combination therapy or after the operation of LV volume reduction. Shimamoto et al 70 reported a case with end-stage non-ischemic dilated cardiomyopathy complicated with AF and LV dyssynchrony, who was successfully treated with the combined use of SAVE, undersized mitral annuloplasty, left atrial Maze procedure with cryoablation, and postoperative biventricular pacing. They noted that CRT was shown to be effective in resolving residual dyssynchrony between the septum and lateral wall after SAVE, wherein a firm, non-compliant Dacron patch was sutured to the septum.…”
Section: Relation To Surgical Therapy For End-stage Hfmentioning
confidence: 99%
“…CRT-P/CRT-D implantation might be useful as a combination therapy or after the operation of LV volume reduction. Shimamoto et al 70 reported a case with end-stage non-ischemic dilated cardiomyopathy complicated with AF and LV dyssynchrony, who was successfully treated with the combined use of SAVE, undersized mitral annuloplasty, left atrial Maze procedure with cryoablation, and postoperative biventricular pacing. They noted that CRT was shown to be effective in resolving residual dyssynchrony between the septum and lateral wall after SAVE, wherein a firm, non-compliant Dacron patch was sutured to the septum.…”
Section: Relation To Surgical Therapy For End-stage Hfmentioning
confidence: 99%
“…When LV dissynchrony becomes evident after surgery (especially LVR), CRT is worthwhile to consider as a treatment. 61 …”
Section: For Abnormal LV Wall Geometry/motionmentioning
confidence: 99%
“…65 Surgery should be considered before inotropic dependency occurs when prior medical treatment has failed. The operative results improve with the selection of the procedure, with elective operation, and mitral plasty for less cardiac dilatation.…”
Section: Non-ischemic Dcm and Lvrmentioning
confidence: 99%